PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 - 2022 - Leovani, Muhammad Rizal; Mariana, Mariana (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The aim of the research is to analyze the effect of good corporate governance (GCG) on the financial performance of banking companies on the IDX. GCG is a system that can carry out regulation, management and supervision when the process controls a business that focuses on transparency, accountability, responsibility, and independence which is expected to increase operational efficiency and investor confidence. This study uses secondary data in the form of annual reports and sustainability reports on banking issuers on the IDX during the period 2020-2022. The independent variables in this study include GCG indicators such as independent board of commissioners, institutional ownership, and managerial ownership, while financial performance as the dependent variable is measured using Return on Assets (ROA). The results of the study show that strong GCG implementation can improve the financial performance of banking companies and help reduce financial risks. This study also contributes to the literature on GCG and the financial performance of banking companies in Indonesia.